Un saltuarius dévot de Jupiter Optimus Maximus dans le Mâconnais - Monique Dondin-Payre; Hélène Chew (Gallia)
The musée d’Archéologie nationale at Saint-Germain-en-Laye has just acquired a bronze wheel-bearing Jupiter with an inscribed base, found at Rontecolon in the locality of Cenves (Rhône). This figurine has been offered to Jupiter Optimus Maximus by a saltuarius, Criciro, and produced by the faber Sabellus. Criciro was an employee of the Prisciacenses, a community whose traces in different records have been followed from Gallo-Roman times to the present day.